The intersection between intellectual property, public health and access to climate-related technologies - Lívia Regina Batista (South Centre, 2023)
On the 20th anniversary of the Doha Declaration on the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) and Public Health adopted by the World Trade Organization, we realize that its impact is beyond issues of public health stricto sensu. The Doha Declaration has inspired discussions at the Council for TRIPS regarding access to climate-related technologies. Climate change is the main and most globalized environmental problem with adverse effects on public health, especially for the vulnerable communities in the Global-South. The main argument of the proponents of the discussion in the TRIPS Council is the need to rebalance public interests (such as public health and environmental/climate issues) with the private/economic interests of the most powerful countries and corporations. This debate addresses both the recognition of intellectual property rights as an important means for the promotion of technological innovation, and the required wider dissemination of technologies - be they medicines or climate-related technologies. This research paper explores the possibilities that the TRIPS Agreement and the Doha Declaration create for international transfer of climate-related technologies. Even though such discussions on climate-related technologies have initially failed in linking climate change and public health, as well as the rhetoric of human rights, the relevance of the topic remains. Besides that, the response to public health issues also must learn from the experience in climate change, such as the case studies evidencing the insufficiency and inefficiency of fast-tracking programs to provide for a wider dissemination of technologies - which have now been widely replicated to address the COVID-19 pandemic. Such comparison can also be an entrance point to discuss the public health implications for the international regime on climate change, highlighting that such issues are deeply intertwined, and need to be addressed jointly as well.
Keywords: 300; Access to Medicines; Climate Change; Climate-related Technologies; COVID-19; Doha Declaration on the TRIPS Agreement and Public Health; Health; Human Rights; Innovation; Intellectual Property; Intellectual Property Rights (IPRs); Pandemic; Public Health; Technology Transfer; TRIPS; TRIPS Agreement; TRIPS Council